HSV-2-Specific Human Female Reproductive Tract Tissue Resident Memory T Cells Recognize Diverse HSV Antigens - Koelle, David M.; Dong, Lichun; Jing, Lichen; Laing, Kerry J.; Zhu, Jia; Jin, Lei; Selke, Stacy; Wald, Anna; Varon, Dana; Huang, Meei-Li; Johnston, Christine; Corey, Lawrence; et al. (Frontiers in Immunology, 2022)
Antigen-specific TRM persist and protect against skin or female reproductive tract (FRT) HSV infection. As the pathogenesis of HSV differs between humans and model organisms, we focus on humans with well-characterized recurrent genital HSV-2 infection. Human CD8+ TRM persisting at sites of healed human HSV-2 lesions have an activated phenotype but it is unclear if TRM can be cultivated in vitro. We recovered HSV-specific TRM from genital skin and ectocervix biopsies, obtained after recovery from recurrent genital HSV-2, using ex vivo activation by viral antigen. Up to several percent of local T cells were HSV-reactive ex vivo. CD4 and CD8 T cell lines were up to 50% HSV-2-specific after sorting-based enrichment. CD8 TRM displayed HLA-restricted reactivity to specific HSV-2 peptides with high functional avidities. Reactivity to defined peptides persisting locally over several month and was quite subject-specific. CD4 TRM derived from biopsies, and from an extended set of cervical cytobrush specimens, also recognized diverse HSV-2 antigens and peptides. Overall we found that HSV-2-specific TRM are abundant in the FRT between episodes of recurrent genital herpes and maintain competency for expansion. Mucosal sites are accessible for clinical monitoring during immune interventions such as therapeutic vaccination.